ANALISIS PENGARUH MODAL, TENAGA KERJA DAN BAHAN BAKU TERHADAP PENDAPATAN PKL NASI BORAN DI KECAMATAN LAMONGAN (JEB17 : Jurnal Ekonomi dan Bisnis, 2022)
The purpose of the study was to find out about the analysis of the effect of capital, labor and raw materials on the income of PKL boran rice in Lamongan District. The variables used in this study are Capital (X1), Labor (X2) and Raw Materials (X3) and Income (Y). Data were collected through questionnaires filled out by boran rice traders in Lamongan District. The sample in this study were 30 respondents. The type of research used is a quantitative method using multiple linear regression analysis, t test, F test with the help of the SPSS program. Based on the results show that all variables, namely Capital, Labor and Raw Materials have a significant effect on the income of boran rice traders in Lamongan District. Based on the results of the t test on the X1 variable, it shows that the capital t count (X1) is 9.062 > t table 2.05183 and the significance value for the modal variable (X1) is 0.000 which is smaller than the level of = 0.05 (0.000 < 0.05). From these results it can be concluded that Capital (X1) has a positive and significant effect on the income of boran rice in Lamongan District. Thus in this study reject the hypothesis H0. Variable X2 shows the t count of labor (X2) is 3.403 > t table 2.05183 and the significance value for the labor variable (X2) is 0.002 which is stated to be smaller than 0.05. From these results, it can be concluded that the labor variable (X2) has a positive and significant influence on the income of boran rice in Lamongan District. Thus in this study reject the hypothesis H0. Variable X3 shows the t count of raw materials (X3) is 3.532 > t table 2.05183 and the significance value for the raw material variable (X3) is 0.002, which is lower than 0.05. From these results, it can be concluded that the raw material variable (X3) has a positive and significant effect on the income of boran rice in Sidokumpul Village, Lamongan District. Thus in this study reject the hypothesis H0. The result of the F test is 224.314 with a significant level of 0.000. Because the significance value is smaller than 0.05. Ha is accepted and H0 is rejected so that capital (X1), labor (X2) and raw materials (X3) together affect the income (Y) of boran rice. in Lamongan District, Lamongan Regency